Psychometric evaluation of the Wheelchair Skills Test Version 5.4.2 in Indian spinal cord injury patients - Anchit Gugnani; Nandini Kushwaha (Bulletin of Faculty of Physical Therapy)
Abstract Background and aim The Wheelchair Skills Test (WST) Version 5.4.2 was developed to assess the performance and safety of wheelchair users. Although earlier versions of the WST have been assessed for their psychometric properties, the reliability and validity of this updated version, which includes revised skill sets and assessment criteria, has not been extensively evaluated in India. The aim of this study was to determine the concurrent validity, inter-rater, and intra-rater reliability of WST Version 5.4.2 among individuals with traumatic spinal cord injuries in India. Methods Twenty-four traumatic spinal cord injury wheelchair users (aged 18–43 years) participated in the study. The sample represented both paraplegic and low tetraplegic wheelchair users who can propel wheelchair, ensuring inclusion of users with varying degrees of functional mobility. Their wheelchair skills were assessed using WST Version 5.4.2, the Spinal Cord Independence Measure (SCIM), and the Visual Analog Scale (VAS). Correlations between these measures were established to evaluate the psychometric properties of the WST. Results The study found no adverse incidents, and the test was well-tolerated. Inter-rater and intra-rater reliability values for the total performance scores were ICC = 0.997 and ICC = 0.995, respectively, while safety scores yielded ICC = 1.0 and ICC = 0.785. Concurrent validity, assessed via Pearson correlation, revealed strong positive correlations between WST scores and both VAS (r = 0.905) and SCIM (r = 0.832). Additional analysis The study included a diverse group of participants with varying levels of experience and skill. The detailed analysis of individual skills revealed specific areas where participants excelled and where they faced challenges. For instance, curb negotiation and ramp navigation were identified as particularly challenging tasks for many participants. To provide a more comprehensive understanding of the results, we have included additional table and figure. Conclusion WST Version 5.4.2 demonstrated excellent inter-rater and intra-rater reliability, along with good concurrent validity, confirming its utility for assessing wheelchair skills in the Indian population.